Distinct adaptation and ancestral retention signals in African and European indigenous cattle genomes - Gao, Junxin; Ginja, Catarina; Liu, Ying; Kantanen, Juha; Ghanem, Nasser; Kugonza, Donald; Makgahlela, Mahlako; Okwasiimire, Rodney; Bovenhuis, Henk; Groenen, Martien A. M.; Crooijmans, Richard P. M. A. (Springer Nature, 2026)
Domestic cattle (Bos taurus and Bos indicus) underpin food security and livelihoods worldwide but face intensifying pressures from climate change, infectious disease, and inconsistent feed supplies. African and European indigenous cattle provide a natural comparative framework spanning gradients of climate, pathogen burden, and husbandry, and possess genomic mosaics comprising African taurine, European taurine, and indicine ancestry. We analyzed whole-genome sequences from 519 cattle across 24 African and European indigenous populations and 117 publicly available genomes from Africa, Asia, Europe, and the Americas. This dataset reveals admixture mosaics among major lineages and identifies 36 candidate genes exhibiting adaptive retention of ancestral alleles associated with response to heat stress (e.g., HSPA12B, DDIT3), immunity (IRAK3), productivity (ACSF3), and reproductivity (SSMEM1, SPEF1). Our study suggests that historical admixture introduced variation shaped by local ecological selection, clarifying how environmental heterogeneity drives the retention of advantageous alleles and informing sustainable breeding and diversity conservation.
Keywords: cattle; genome; sequencing; European breeds; African breeds; genetic resources